2011
DOI: 10.1371/journal.pone.0022954
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Food Intake, Obesity and Inflammation Process in Zucker fa/fa Rat Pancreatic Islets

Abstract: Inappropriate food intake-related obesity and more importantly, visceral adiposity, are major risk factors for the onset of type 2 diabetes. Evidence is emerging that nutriment-induced β-cell dysfunction could be related to indirect induction of a state of low grade inflammation. Our aim was to study whether hyperphagia associated obesity could promote an inflammatory response in pancreatic islets leading to ß-cell dysfunction. In the hyperphagic obese insulin resistant male Zucker rat, we measured the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
5
15
0
1
Order By: Relevance
“…Pancreatic islets from patients with type 2 diabetes are infiltrated with macrophages (7,8), express elevated proinflammatory cytokines (9,10), and express features of fibrosis (11), consistent with reports from animals and primates with this disease (7,(12)(13)(14)(15)(16)(17)(18). The detrimental effects of inflammation on islet b-cell function were recently confirmed, when the interleukin (IL)-1 receptor antagonist reduced hyperglycemia and improved b-cell insulin secretion in patients with type 2 diabetes (1).…”
supporting
confidence: 76%
“…Pancreatic islets from patients with type 2 diabetes are infiltrated with macrophages (7,8), express elevated proinflammatory cytokines (9,10), and express features of fibrosis (11), consistent with reports from animals and primates with this disease (7,(12)(13)(14)(15)(16)(17)(18). The detrimental effects of inflammation on islet b-cell function were recently confirmed, when the interleukin (IL)-1 receptor antagonist reduced hyperglycemia and improved b-cell insulin secretion in patients with type 2 diabetes (1).…”
supporting
confidence: 76%
“…In type 2 diabetes, mitochondrial dysfunction in the tissues, particularly in the pancreas, due to proinflammatory responses and disturbance in redox homeostasis signaling have also been reported which may lead to increased oxidative stress [7,32,33]. Our previous studies on type 1 and type 2 diabetic rat models have also suggested that increase in oxidative stress is associated with increased mitochondrial dysfunction [13,14,15,17].…”
Section: Discussionmentioning
confidence: 99%
“…The ZDF rats exhibit progressive metabolic complications associated with increased insulin resistance, oxidative and nitrosative stress [3,4,5,6]. Studies have shown that obesity, inflammatory cytokines, excessive food intake are risk factors for development of hyperglycemia, insulin resistance and pancreatic β-cell dysfunction in ZDF rats when compared to Zucker lean controls (ZL,FA/+) [7]. The precise molecular mechanism that links progressive metabolic syndrome and insulin resistance in different tissues of ZDF rats is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…15 Afterward, we sought to analyze body weight and adiposity on different groups, since there is a direct relationship between the increase of adiposity and malfunction of pancreatic β-cells. 16,17 As observed, trained groups presented reduced adiposity compared with sedentary groups with what could reflect positively on glycemic homeostasis and/or malfunction of pancreatic islets. The lack of significant differences between groups T and AT and S and AS seems to be directly related to chronic effects.…”
Section: Resultsmentioning
confidence: 65%